Leadership Styles and Organizational Citizenship Behavior for the Environment: The Mediating Role of Self-Efficacy and Psychological Ownership - Ullah, Irfan; Wisetsri, Worakamol; Wu, Hao; Shah, Syed Mehmood Ali; Abbas, Ali; Manzoor, Shahid (Frontiers in Psychology, 2021)
Change and environmental patterns are having an immense effect upon the world. Businesses, communities, and even individuals are struggling to perform their role within environmental protection. This paper investigates the role of leadership styles on organizational citizenship behavior for the environment (OCBE) directly and through the mediation of self-efficacy and psychological ownership. The survey technique was used to collect the data from Chinese banking, insurance, medicine, and teaching service sector employees for the current study. The reliability and validity of the scale items were tested. This study used AMOS-SEM for data analysis and testing the developed hypotheses. The empirical results confirmed that responsible, inclusive, authentic, and supportive leadership styles positively impact employees' OCBE. The results further confirm that self-efficacy and psychological ownership act as mediators between leadership and OCBE. The current study widens our understanding of leadership styles and their impact on OCBE, along with limitations associated with the study and future guidelines for investigators.